Beyond Boundaries: Millennial Women and the Opportunities for Global Leadership. Issue 4 (April 2017) - Stefanco, Carolyn J.
Abstract : Although much of the literature on globalization focuses on the field of business and the overwhelming majority of world leaders are male, global growth in all sectors requires women's full participation. Older generations of women were discouraged from seeking international assignments, but millennial women are more likely than men to have the education, experience, and interests required in the global arena. With few exceptions, corporations and other organizations are not doing a good job of preparing global leaders. Recent scholarship, however, points the way for millennial women to develop their own global competencies, which will position them for career success.